"Don't let anybody ever put you down culturally…. it's not good…": Creating spaces for Blak women's healing. Issue 3 (1st August 2022) - Balla, Paola; Jackson, Karen; Quayle, Amy F; Sonn, Christopher C; Price, Rowena K
Abstract: Research has highlighted the importance of Indigenous knowledge and cultural practice in healing from ongoing histories of trauma, dispossession, and displacement for Indigenous peoples in Australia and elsewhere. Connection with culture, Country, and kinship has been identified as protective factors for Aboriginal social and emotional well‐being and as facilitating cultural healing. This paper draws on stories mediated through cultural practice specifically, Wayapa and bush‐dyeing workshops, to explore how women resignified experiences and engaged in "healing work." Our collaborative analysis of the stories shared resulted in three main themes that capture dialogs about the need for culturally safe spaces, vulnerability and identity, and culture, Country, and place. Centering Aboriginal knowledge, our analysis shows the meanings of Country, spirituality, and the coconstitution of people, culture, and the natural environment. Through Indigenous cultural practice, the women "grew strength in relationship" as they engaged in the psychosocial processes of deconstruction, reclamation, and renarrating personal and cultural identities. Highlights: Aboriginal communities continue to experience historical trauma and ongoing structural violence. Aboriginal people have expressed the need to understand the impacts of colonial dispossession. Unpacking systems of oppression and cultural reclamation is central to decolonization and healing. Embodied cultural practices allow Aboriginal women to yarn about culture and Country. Relationship building is central to empowering inquiry as healing.